The integrative process promoted by EMDR in dissociative disorders: neurobiological mechanisms, psychometric tools, and intervention efficacy on the psychological impact of the COVID-19 pandemic - Poli, Andrea; Cappellini, Francesco; Sala, Josephine; Miccoli, Mario (Frontiers in Psychology, 2023)
Dissociative disorders (DD) are characterized by a discontinuity in the normal integration of consciousness, memory, identity, emotion, perception, bodily representation, motor control, and action. The life-threatening coronavirus disease 2019 (COVID-19) pandemic has been identified as a potentially traumatic event and may produce a wide range of mental health problems like depression, anxiety disorders, sleep disorders, and DD, stemming from pandemic-related events such as sickness, isolation, losing loved ones, and fear for one's life. In our conceptual analysis we introduce the contribution of the structural dissociation of personality (SDP) theory and polyvagal theory to the conceptualization of COVID19 pandemic-triggered DD and the importance of assessing perceived safety in DD through neurophysiologically-informed psychometric tools. In addition, we analyze the contribution of Eye Movement Desensitization and Reprocessing (EMDR) to the treatment of COVID19 pandemic-triggered DD and suggest possible neurobiological mechanisms of action of EMDR. In particular, we propose that through slow eye movements, EMDR may promote an initial NREM-sleep-stage 1-like activity, a subsequent access to a slow wave sleep activity, and an oxytocinergic neurotransmission that, in turn, may foster the functional coupling between paraventricular nucleus and both sympathetic and parasympathetic cardioinhibitory nuclei.Neurophysiologically-informed psychometric tools for safety evaluation in dissociative disorders are discussed. Furthermore, clinical and public health implications are considered, combining EMDR, SDP theory and polyvagal conceptualizations, in light of the potential dissociative symptomatology triggered by COVID19 pandemic.